The potential effect of Garlium GEM HCTM as a tick control agent in cattle - Stoltsz, Wilhelm Heinrich (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Science Tropical Animal Health))--University of Pretoria, 2022.